Impact of prior accumulated work and intensity on power output in elite/international level road cyclists - a pilot study - Leo, P.; Giorgi, A.; Spragg, J.; Martinez Gonzalez, B.; Mujika, I. (German Journal of Exercise and Sport Research, 2022)
Background: This study aimed to investigate the impact of the intensity of prior accumulated work on the decline in power output in elite/international level road cyclists, comparing the effects of prior continuous moderate intensity versus intermittent high intensity cycling. Methods: Nine elite/international level road cyclists (age 26.2± 4.0 years; body mass: 66.6± 5.5kg; height: 176± 0.4cm) conducted a 12-min field test (12minfresh) during two consecutive training camps. Participants then performed both a 150-min moderate intensity continuous (MIC) work bout or a 150-min high intensity intermittent (HII) race simulation in randomized order, cross-over design. After each condition a 12-min field test (12minfatigue) was completed. Results: Absolute and relative 12minfresh power output were not significantly different between training camps (p> 0.05). The 12minfatigue power after HII was significantly lower than 12minfatigue after MIC (delta= 14W; p= 0.014). Participants recorded more percentage time (%Time) in heart rate (HR) zone 3 (delta= 9.2%; p= 0.003) and power output band between 5.0-7.9W ·kg-1 (delta= 8.9%; p= 0.002) as well as higher total work (delta= 237kJ; p= 0.001) during HII. Conclusion: These findings reveal that the decline in power output is higher after HII compared to MIC cycling work bouts. This suggests that the quantification of total work and intensity should be used in conjunction to predict a distinctive decline in power output. Future research is required to better understand the mechanisms of endurance "durability" in elite/international level road cyclists.